2000
DOI: 10.1046/j.1365-2427.2000.00531.x
|View full text |Cite
|
Sign up to set email alerts
|

Movements of adult fish in a hybrid zone revealed by microsatellite genetic analysis and capture‐recapture data

Abstract: Summary Barbus barbus and Barbus meridionalis (Cyprinidae) form a hybrid zone in the Lergue river (southern France). We attempted to characterise the pattern of adult dispersal with the aim of understanding the evolutionary interactions maintaining this hybrid zone. In a previous capture/recapture study, movements between localities at a distance of 2.5 km or more appeared extremely rare. We therefore decided to investigate adult movement using a different method, based on genetic markers. As this hybrid zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 22 publications
(31 reference statements)
2
20
1
Order By: Relevance
“…Studies based on morphology, osteology, ecology and, to a lesser extent, on genetics, have all made contributions to the present understanding of the Barbus genus Granado-Lorencio, 1988, 1997;CollaresPereira and Madeira, 1990;Torralva et al, 1997;Aparicio and Sostoa, 1998;Chenuil et al, 1998Chenuil et al, , 2000Tsigenopoulos et al, 1999, Callejas andOchando, 2000;Tsigenopoulos and Berrebi, 2000). However, basic questions on its evolutionary differentiation remain unsolved (see Tsigenopoulos and Berrebi, 2000 and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Studies based on morphology, osteology, ecology and, to a lesser extent, on genetics, have all made contributions to the present understanding of the Barbus genus Granado-Lorencio, 1988, 1997;CollaresPereira and Madeira, 1990;Torralva et al, 1997;Aparicio and Sostoa, 1998;Chenuil et al, 1998Chenuil et al, , 2000Tsigenopoulos et al, 1999, Callejas andOchando, 2000;Tsigenopoulos and Berrebi, 2000). However, basic questions on its evolutionary differentiation remain unsolved (see Tsigenopoulos and Berrebi, 2000 and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence for both exogenous selection (B. barbus is unable to live in typical B. meridionalis habitats and a capture-marked-recapture study demonstrated marked differences in survival between upstream and downstream sites (Crespin et al, 2002); and endogenous selection (eg more than 50% of experimental F1 hybrids are unviable or sterile; Philippart and Berrebi, 1990;Crespin, 1996). Clines along the hybrid zone were detected using diagnostic allozymic (Crespin and Berrebi, 1994; nine locations) and microsatellite loci (Chenuil et al, 2000; five locations). The introgression index was calculated as the percentage of alleles diagnostic of B. meridionalis in a given population (100% for a pure B. meridionalis population, 0% for a pure B. barbus).…”
Section: Methodsmentioning
confidence: 99%
“…The upstream station, Cartel, had an allozymic introgression index (defined above, see also below) of about 60% in 1992 (Crespin and Berrebi, 1994) and an average microsatellite introgression index of about 40% in 1993-1995 (Chenuil et al, 2000), whereas the downstream location, Saint-Fréchoux, had a 40% introgression index with allozymes in 1992 and around 20% with microsatellites in 1993-1995. For each station, samples were taken in spring (the spawning season) and in winter, and were analysed with either allozymes or microsatellite loci (Table 1).…”
Section: Samples and Locationsmentioning
confidence: 99%
See 2 more Smart Citations